Latin American income tax systems and current double taxation agreements - Espinosa Sepúlveda, Jorge (2014)
Tax systems in Latin America have played a very important role as the main, and in some cases the only, means of obtaining revenue to finance the major public expenditure that is necessary for the work of the states through time. Below is a short review of the main aspects of tax systems in the región, with emphasis on the impact of taxes on income in force in the majorLatin American countries, as well as a brief explanation of the network of agreements to avoid double taxation that are in force in each of them.